Electrophysiological dynamics of antagonistic brain networks reflect attentional fluctuations - Aaron Kucyi (Nature Portfolio, 2020)
Brain imaging studies suggest that specific, large-scale, cortical networks show antagonistic activity with one another. Here, the authors studied the dynamics of these networks using implanted electrodes in the human brain, revealing that the coordination of inter-network dynamics on fast time scales relates to fluctuations in attention.